The Effect of Institutional Ownership, Audit Opinion, KAP Reputation, Management Changes and Audit Delay on Auditor Switching - Keumala Hayati; Junianto Sihotang; Apridita Lubis; Dinamis Halawa (Journal Research of Social Science, Economics, and Management, 2021)
This study aims to determine the effect of institutional ownership, audit opinion, hood reputation, management turnover, and audit delay on auditor switching in manufacturing companies on the IDX in 2017-2020. This research is quantitative descriptive. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This sampling used the purposive sampling method with the number of samples obtained as many as 123 companies. The data analysis technique used is logistic regression analysis (logistic regression). The study results show that institutional ownership, reputation, and audit delay partially have a significant effect on auditor switching. In contrast, audit opinion and management change partially have no considerable impact on auditor switching. However, simultaneously institutional ownership, audit opinion, hood reputation, management turnover, and audit delay significantly affect auditor switching.